Chienne, truie, renarde, belette… - Michel Briand (Cahiers Mondes Anciens)
This paper is a study of the speeches ascribed to female animals, in Aesopic fables, as well as in Semonides, Hesiod or Archilochus. Pragmatic and cognitive definitions of metaphors and of comical paradoxes help showing that these speaking female figures participate in building up ethical representations which are strengthened by the tension of some characters in the fable with the implicit discurse of the fabulist (ainos, logos or muthos), as well as, in the later collections, with the additional moral (epimuthion). In Aesopic fables, some significant figures have different functions, depending on whether the species has a female grammatical gender or not, and whether their speeches agree or contradict the fabulist : sow, bitch, dove, crow, swallow, hyena, weasel, vixen…